2006
DOI: 10.1002/chem.200501485
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Highly Functionalized Tetrahydroxanthenols—Unprecedented Access to Privileged Structural Motifs

Abstract: Tetrahydroxanthenones, which can be easily prepared by a domino oxa-Michael aldol condensation, offer various possibilities for diastereoselective functionalization, giving access to the stereocontrolled synthesis of stereochemical triades or tetrades, which represent privileged structural motifs. In most cases, the relative stereochemistry was unequivocally established by crystal structure analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 63 publications
0
18
0
1
Order By: Relevance
“…[218] A closely related reaction that involves the use of IBX in the presence of InCl 3 leads to a,b-unsaturated lactones. [219] The cyclization of unsaturated N-aryl amides in the presence of IBX represents a reaction type, the synthetic potential of which has certainly not yet been fully explored. Detailed studies by Nicolaou et al demonstrated that CÀN bond formation occurs at elevated temperature through a reactivity of IBX that is fundamentally different from most of the reactions discussed previously.…”
Section: Miscellaneous Reactions Of Ibxmentioning
confidence: 99%
“…[218] A closely related reaction that involves the use of IBX in the presence of InCl 3 leads to a,b-unsaturated lactones. [219] The cyclization of unsaturated N-aryl amides in the presence of IBX represents a reaction type, the synthetic potential of which has certainly not yet been fully explored. Detailed studies by Nicolaou et al demonstrated that CÀN bond formation occurs at elevated temperature through a reactivity of IBX that is fundamentally different from most of the reactions discussed previously.…”
Section: Miscellaneous Reactions Of Ibxmentioning
confidence: 99%
“…[38,39] This cascade reaction leads directly to formyl chromene 13, which can then be converted into diene 7a with a Wittig reaction (Scheme 2), as demonstrated in previous work from our group. Another route to diene 7, which has an unsubstituted benzochromone scaffold, involves a domino oxa-Michael-aldol reaction of the corresponding salicylaldehyde with prenal, as described previously.…”
Section: Resultsmentioning
confidence: 63%
“…[218] Eine verwandte Reaktion mit IBX in Gegenwart von InCl 3 führt zur Bildung a,b-ungesättigter Lactone. [219] Eine Reaktion, deren Synthesepotenzial noch nicht annähernd offenbart wurde, ist sicherlich die Cyclisierung von ungesättigten N-Arylamiden in Gegenwart von IBX. Nicolaou et al haben in detaillierten Studien gezeigt, dass bei er-Schema 59.…”
Section: Weitere Reaktivitäten Von Ibxunclassified